Scrunitizing religious-based reform: Insight from indonesia prisons - Hamja Hamja; Eri Eka Sukarini (International Journal Reglement & Society (IJRS), 2022)
In the development of the prison system in the world, the element of religiosity has become a vital value that has a significant impact on changing the behavior of criminals in prison. Therefore, in a number of prisons in the world, religious-based reform activities are the main aspect in the effort to reform prisoners’ behavior. This study aims to analyze the impact of implementing religion-based reform programs in Indonesian prisons. The method used in this research is a qualitative method, with a case study approach. The sample used is a number of prisons in Indonesia that implement a religion-based reform program in order to encourage changes in the behavior of inmates in prison. Data was collected by using open interview techniques and time recording observations to produce comprehensive data and be able to provide a holistic picture. The results of this study indicate that the religion-based prisoners reform program shows significant impacts on prisoners’ behavioral change, which is indicated by the low recidivism rate in ex-convicts underwent religion-based reform programs during their sentence, the decreased rate of violence in prisons, and the increasing number of prisoners who receive remissions for good behavior after undergoing a religion-based reform program